2017
DOI: 10.1186/s13014-017-0802-3
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of LncRNA TUG1 enhances radiosensitivity in bladder cancer via suppressing HMGB1 expression

Abstract: BackgroundLong non-coding RNAs (lncRNAs) have been reported to regulate the sensitivity of different cancer cells to chemoradiotherapy. Aberrant expression of lncRNA Taurine-upregulated gene 1 (TUG1) has been found to be involved in the development of bladder cancer, however, its function and underlying mechanism in the radioresistance of bladder cancer remains unclear.MethodsQuantitative real-time PCR (qRT-PCR) was conducted to measure the expression of TUG1 and HMGB1 mRNA in bladder cancer tissues and cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(56 citation statements)
references
References 34 publications
3
53
0
Order By: Relevance
“…found that the downregulation of HMGB1 modulated telomere homeostasis and increased the radiosensitivity of human breast cancer cells. Simultaneously, some researchers believe that this phenomenon may also be related to the regulation of autophagy, apoptosis, or membrane receptor signaling pathways by HMGB1 . In our study, we found that the expression of HMGB1 was significantly higher in ESCC tissues than in adjacent normal tissues (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…found that the downregulation of HMGB1 modulated telomere homeostasis and increased the radiosensitivity of human breast cancer cells. Simultaneously, some researchers believe that this phenomenon may also be related to the regulation of autophagy, apoptosis, or membrane receptor signaling pathways by HMGB1 . In our study, we found that the expression of HMGB1 was significantly higher in ESCC tissues than in adjacent normal tissues (Fig.…”
Section: Discussionsupporting
confidence: 58%
“…TUG1 is a critical regulator of cell proliferation in several cancer types, such as glioblastoma (35), osteosarcoma (26), bladder cancer (36) and colorectal cancer (37). TUG1 participates in the proliferation, migration, invasion and apoptosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the discovery of effective therapeutic targets to enhance radiosensitivity may improve the survival of ESCC patients. The overexpression of HMGB1 has been implicated in multiple cancers, including breast (18), rectal (11), bladder (19) and gallbladder cancer (20), pleural mesothelioma (21), nasopharyngeal carcinoma (22), and esophageal cancer (23). During tumor development and cancer treatment, diverse roles for HMGB1 have been revealed in previous studies, including roles in inflammation (24), immune responses (25), angiogenesis (26), DNA damage repair (27), autophagy (28), proliferation, apoptosis, invasion and metastasis (29,30).…”
Section: Discussionmentioning
confidence: 99%